Side-chain effects on N-type organic thermoelectrics: A case study of fullerene derivatives. (October 2018) - Liu, Jian; Qiu, Li; Portale, Giuseppe; Torabi, Solmaz; Stuart, Marc C.A.; Qiu, Xinkai; Koopmans, Marten; Chiechi, Ryan C.; Hummelen, Jan C.; Anton Koster, L. Jan
Abstract: In this contribution, the two key parameters, the polarity and side chain length have been changed to study their effects on n-type organic thermoelectrics of a series of fullerene derivatives. Fullerene derivatives bearing either an alkyl side chain or ethylene glycol (EG) side chains of different lengths are used as the host molecules for molecular doping. It is found that the polar EG side chains can enable better miscibility with the polar dopant than the alkyl side chain, which leads to more than 5-fold enhancement of doping efficiency. Beyond the doping efficiency, another crucial parameter of molecular doping, the molecular order, is readily acquired by simultaneous control of the polarity and the length of the side chain. A polar side chain with an appropriate chain length can contribute to increasing Seebeck coefficients of doped fullerene derivatives more effectively than an alkyl side chain, likely due to the resultant good miscibility and high molecular order. As a result, an optimized power factor of 23.1 μW m -1 K -2 is achieved in the fullerene derivative with a tetraethylene glycol side chain. This represents one of the best n-type organic thermoelectrics. Additionally, EG side chains can improve the air stability of n-doped fullerene derivatives films as compared to an alkyl side chain. Our work sheds light on the design of side-chains in efficient n-type small molecules thermoelectric materials and contributes to the understanding of their thermoelectric properties. Graphic abstract: fx1 Highlights: The effects of the polarity and the side chain length of fullerene derivatives on the n-type thermoelectrics are investigated. Molecular order of doped films can be improved by simultaneous control of the polarity and side chain length. A high power factor of 23.1 μW m -1 K -2 is achieved in this study, which represents one of the best results.